Institutions and economic growth: The successful experience of Switzerland (1870 - 1950) - Thomas David; André Mach (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This research paper discusses the role of institutions in the rapid growth and successful international integration of Switzerland during the late nineteenth and early twentieth century. In analysing the emergence and consolidation of the institutions whose existence was crucial, the paper looks both at the political institutions that managed conflicts and promoted cooperation between private and public actors and the economic institutions that, on the one hand, compensated the groups that fell behind in the developmental process (e.g., agricultural subsidies, high tolerance for domestic cartels, tariffs for some industries, institutions for labour representation) and, on the other hand, enhanced productivity. In addition, the absence of some institutions such as a patent law and an independent central bank was also crucial in the Swiss case, even though these two institutions are regarded as pre-requisites of development by today's economic orthodoxy. The paper concludes by drawing lessons for today's developing countries.
Keywords: N13; N23; N43; 330; economic growth; institutions; Switzerland; small countries; Wirtschaftswachstum; Institutionalismus; Kleines-Land-Modell; Schweiz